Dimming the day : evening meditations for quiet wonder - Grant, Jennifer (Broadleaf Books, 2021)
The moon is out, the air has cooled, you are ready for bed. You know that scrolling on your phone does not draw you toward sleep. Power down your phone, take a breath, and begin to dim the day. Author Jennifer Grant offers gentle meditations that help you direct your gaze away from screens and toward the natural world. Replace anxiety with awe, distraction with focus, and worry with true rest.